The Impact of Organizational Commitment, Incentive, and Risk Reporting through Social Media on Whistleblowing Intention - Alim Dhisa Istiqomah; Inanda Shinta Anugrahani (Jurnal Dinamika Akuntansi, 2024)
Purposes: This study explores the impact of organizational commitment, incentives, and risks associated with reporting through social media on whistleblowing intentions. Methods: A quantitative survey approach was adopted to collect data from accounting, finance, and tax employees in 40 profit-oriented companies. The garnered data were analyzed using multiple linear regression analysis through SPSS version 26. Findings: Research results indicate that organizational commitment has a positive and significant influence on whistleblowing intentions, while incentives have been observed to have no significant effect. The risk variable for reporting via social media does not show a negative influence that can reduce whistleblowing motivation. Whistleblowing intentions continue to occur because of the high loyalty of respondents, which overrides the provision of incentives and the risk of threats. This research contributes to organizations by providing guidance on creating whistleblowing policies that promote positive reporting to reveal fraud and collar crime. Novelty: The study focuses on the increasing number of fraud cases, particularly corruption, in Indonesia and the importance of whistleblowing on social media to expose organizational violations. Employee perceptions regarding combining financial and non-financial incentives, and whistleblowing risks in social media are rarely discussed so it is explained in this study.